Interaksi Komunitas Sisterfillah Bandung Timur Dalam Menyebarkan Dakwah Islam Di Kalangan Muslimah - Lina, Risalina; Rahman, Encep Taufik; Wahyudin, Aep; Muhammad Abdul Ghani, Agi (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study aims to find out the tabligh bil-khitobah strategy carried out by the Muslim pearl community. With the intended aspects, namely regarding the formulation, steps, and methods of tabligh bil khitobah. The theories used are Fred R. David's management strategy theory, Lasswel's communication science theory, and al-Bayanuni's da'wah strategy theory. The research method is a qualitative descriptive method that uses a qualitative approach. The results of the study show that the Muslim pearl community formulates khitobah by planning visions and missions, programs, and themes, implementation by promoting and carrying out planned activities, and evaluation to find out the weaknesses of activities. Khitobah steps by determining missionaries, knowing the characteristics of members, the necessary media or tools, and khitobah materials that are in accordance with the needs. And three methods of khitobah are sentimental strategy, rational strategy, and sensory strategy.